Therapeutic Effects of Inhibitor of ompA Expression against Carbapenem-Resistant Acinetobacter baumannii Strains - Seok-Hyeon Na (MDPI AG, 2021)
The widespread of carbapenem-resistant Acinetobacter baumannii (CRAB) is of great concern in clinical settings worldwide. It is urgent to develop new therapeutic agents against this pathogen. This study aimed to evaluate the therapeutic potentials of compound 62520, which has been previously identified as an inhibitor of the ompA promoter activity of A. baumannii, against CRAB isolates, both in vitro and in vivo. Compound 62520 was found to inhibit the ompA expression and biofilm formation in A. baumannii ATCC 17978 at sub-inhibitory concentrations in a dose-dependent manner. These inhibitory properties were also observed in clinical CRAB isolates belonging to sequence type (ST) 191. Additionally, compound 62520 exhibited a bacteriostatic activity against clinical clonal complex (CC) 208 CRAB isolates, including ST191, and ESKAPE pathogens. This bacteriostatic activity was not different between STs of CRAB isolates. Bacterial clearance was observed in mice infected with bioimaging A. baumannii strain 24 h after treatment with compound 62520. Compound 62520 was shown to significantly increase the survival rates of both immunocompetent and neutropenic mice infected with A. baumannii ATCC 17978. This compound also increased the survival rates of mice infected with clinical CRAB isolate. These results suggest that compound 62520 is a promising scaffold to develop a novel therapeutic agent against CRAB infections.